Innovative approaches in lung tissue engineering: the role of exosome-loaded bioscaffolds in regenerative medicine - Torkashvand, Mohammad; Rezakhani, Leila; Habibi, Zahra; Mikaeili, Abdolhamid; Rahmati, Shima (Frontiers in Bioengineering and Biotechnology, 2024)
Lung diseases account for over four million premature deaths every year, and experts predict that this number will increase in the future. The top cause of death globally is diseases which include conditions like lung cancer asthma and COPD. Treating severe acute lung injury is a complex task because lungs struggle to heal themselves in the presence of swelling inflammation and scarring caused by damage, to the lung tissues. Though achieving lung regeneration, in controlled environments is still an ambition; ongoing studies are concentrating on notable progress, in the field of lung tissue engineering and methods for repairing lung damage. This review delves into methods, for regenerating lungs with a focus on exosome carry bioscaffolds and mesenchymal stem cells among others. It talks about how these new techniques can help repair lung tissue and improve lung function in cases of damage. Also noted is the significance of ex vivo lung perfusion (EVLP), for rejuvenating donor lungs and the healing properties of exosomes in supporting lung regeneration.